"Just like a natural man": The B.D. styles of Gertrude "Ma" Rainey and Bessie Smith. Issue 2 (3rd April 2019) - Hammer, K. Allison
Abstract: This article pays homage to the antique term "B.D. (bulldyke) Woman" of the 1920s and 1930s, at a moment when the rise of a universal queer subject threatens to erase specific lesbian histories. Characterized by an aggressive stance and an enormousness that confronts rather than merely protests, Black B.D. artists "stole" both masculinity and White privilege to accumulate power and cultural capital. B.D. is therefore a multilayered response to sexism, racism, and homophobia. This performance style is a product of outrage at the oppressive conditions that marked the legacy of slavery, to which B.D. blues must be viewed as a response rather than a more static sexual aesthetic style belonging to lesbian women. Such masculine bravado in Black women disrupted gender/sex alignments and notions of cisnormativity embedded in African American communities. In order to think through this historical legacy, I perform close readings of song lyrics performed by Gertrude "Ma" Rainey and Bessie Smith. The rejection of oppressive conditions occurs most acutely through the theme of travelling in songs that decenter racialized and heteronormative conceptions of home. Through this theme, Rainey and Smith expanded the phallic possibilities of their time period, and for the 2010s, these artists tamper with our staid notions of what gender, sex, and sexuality have meant in the past.